Urban growth in Southern Africa : comparing 30 years of decadal imagery to census data - Lewis, Lauren Lyn (Department of Environmental and Geographical Science, 2015)
The total urban area of each study site was calculated for each time slice and the results were represented as maps depicting urban expansion. Graphs were also created depicting the total urban area vs. total population for each time slice (1970s, 1990s and 2000s).